Nitrate Transport and Distribution in Soybean Plants With Dual-Root Systems - Li, Sha; Xiao, Fengsheng; Yang, Daocheng; Lyu, Xiaochen; Ma, Chunmei; Dong, Shoukun; Yan, Chao; Gong, Zhenping (Frontiers in Plant Science, 2021)
Nitrate absorbed by soybean (Glycine max L. Merr.) roots from the soil can pro-mote plant growth, while nitrate transported to nodules inhibits nodulation and nodule nitrogen fixation activity. The aim of this study was to provide new insights into the in-hibition of nodule nitrogen (N) fixation by characterizing the transport and distribution of nitrate in soybean plants. In this research, pot culture experiments were conducted using a dual root system of soybeans. In the first experiment, the distribution of 15N de-rived from nitrate was observed. In the second experiment, nitrate was supplied-withdrawal-resupplied to one side of dual-root system for nine consecutive days, and the other side was supplied with N-free solution. Nitrate contents in leaves, stems, peti-oles, the basal root of pealed skin and woody part at the grafting site were measured. Nitrate transport and distribution in soybean were analyzed combining the results of two experiments. The results showed that nitrate supplied to the N-supply side of the dual-root system was transported to the shoots immediately through the basal root pealed skin (the main transport route was via the phloem) and woody part (transport was chief-ly related to the xylem). There was a transient storage of nitrate in the stems. After the distribution of nitrate, a proportion of the nitrate absorbed by the roots on the N-supply side was translocated to the roots and nodules on the N-free side with a combination of the basal root pealed skin and woody part. In conclusion, the basal root pealed skin and woody part are the main transport routes for nitrate up and down in soybean plants. Ni-trate absorbed by roots can be transported to the shoots and then retranslocated to the roots again. The transport flux of nitrate to the N-free side was regulated by transient storage of nitrate in the stems.